Academic Help Seeking Behavior Among Students in Higher Education: Assessment for Counseling - Chairani, Lisya; Raudatussalamah, Raudatussalamah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Help-seeking behavior is an important and fundamental strategy for successful learning when knowledge and understanding are not able to solve problems. This descriptive qualitative research aims to obtain an overview of the patterns of help- seeking behavior applied by students of the psychology faculty of UIN SUSKA. The respondents of this study were 112 students representing semesters 3, 5, 7, 9, and 11. Data collection was carried out using an open ended questionare. The data obtained were then coded to create categories and analyzed. Furthermore, the answers are determined based on their frequency and the effect is seen if it is related to the GPA value. The results showed that the pattern of student behavior in seeking help was as follows: tends to optimize external sources such as asking friends and lecturers. When facing difficulties, students will emphasize instrumental help, namely by reading books or not asking for help at all. The type of assistance that is often needed is material assistance in the form of reference loans, providing assistance to do and asking others to show how to do the task. The figures who are often asked for help are friends. The reason for choosing figures is based on cognitive considerations, such as providing solutions, having the competence to help. The strategy used to optimize the help that has been obtained is to make time arrangements. Keywords: help-seeking, academic difficulties